Implementasi Game 2D Edukasi Pengetahuan Islam untuk Remaja Menggunakan Unity - Akbar, Yuma; Albahy, Abdurrahman Asyam (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This research aims to address the lack of interest among children in learning basic Islamic knowledge through conventional learning methods, which are often perceived as boring. The proposed solution is the development of Unity-based educational 2D games that present basic Islamic knowledge in an engaging and interactive way. The target audience for this research is children aged 12–15 years, who are expected to show greater interest and motivation to learn Islam through more enjoyable media. The methodology employed in this research is the Waterfall method, consisting of the stages of needs analysis, system design, implementation, verification, and maintenance. The tools used include Unity software for game development and Visual Studio for C# coding. The study also utilized surveys and observations to measure the game’s effectiveness in enhancing children’s knowledge and engagement. Through efficient project management, it is anticipated that this educational game will become an effective and engaging learning tool for children, while contributing significantly to the field of Islamic religious education.